Ministry of Trade and Industry Decree No. 1263 Of The Year 2016 On the Continuation of Imposing Export Duty on the Exports of Nitrogen Fertilizers = وزارة التجارة والصناعة قرار رقم 1263 لسنة 2016 فى شأن استمرار فرض رسم صادر على الصادرات من الأسمدة الأزوتية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic